FAKTOR - FAKTOR YANG MEMPENGARUHI BELANJA MODAL PADA KABUPATEN / KOTA DI PROVINSI JAWA TENGAH - Candra Kusumawati, 16.05.62.0039; Maryono, Maryono (Students' Journal of Accounting and Banking, 2018)
ABSTACT The prupose of this study are determine the generally allocation funds, special allocation funds andsharing funds for capital expenditures. The population in this study is Regency/City in Central Java province witch consists of 29 Regencies and 6 cities. Secondary data is used inthis study with the form of APBD realization report of Regency/City in Central Java Province in 2014 until 2016. This research uses multiple linear regression analysis. The result of the study shows that the generally allocation funds, special allocation funds and sharing funds give positive influence on capital expenditure. Keywords: the generally allocation funds, the special allocation funds, the sharing funds for capital expenditures